Feedlot and milo stubble fattening tests with feeder lambs. - Bell, T.D.; Erhart, A.B. (Kansas Agricultural Experiment Station, 2012)
The lambs in this year's experiment’s were secured directly from the mountain range in Southern Utah, and included Columbia-Rambouillet crosses as well as lambs of Suffolk-Ramhouillet breeding. They averaged 76 pounds at the range shipping point and 68 pounds-off the cars at Garden City; after a period of 50 days of pasture and roughage feeding they were started on the experimental tests weighing 78 pounds. The lambs were lotted into eight groups of 60 lambs each and given Standard western rations of sorghum stover, sorghum grain, protein supplement, and limestone. After two lots of lambs reached an average daily grain ration of 1 pound per head ,they were turned into milo stubble. One lot was given alfalfa. hay as a supplement and the other lot was given soybean pellets.
Keywords: Sheep; Feedlot; Milo; Performance